2021
DOI: 10.1002/pc.26074
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and characterization of novel silicone/natural fabric/graphene‐based functional composites for human body motion sensing

Abstract: This study focuses on the development of strain‐sensors utilizing biodegradable natural fabrics (cotton, flax, and wool) and graphene nanoplatelets (GN) through novel coating techniques. A systematic study on improving the electrical conductivity of natural fiber fabrics to be used as effecting sensing stimuli was conducted by varying the proportions of graphene. To further enhance the conductivity, GN was hybridized with conducting polymers, such as polypyrrole (PPy), polyaniline (PANI), and with carbon black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…Additionally, the conductivity continued to improve with the increase in the GNP concentration in the paste, which agrees with observations reported in other works [19][20][21]24]. This improvement can be because the incorporation of GNPs has created a path for the electricity flow, and increasing the concentration of the nanoparticles might have resulted in the formation of a better conductive network, which eased the flow of electrons, leading to the linear rise in the electrical conductivity [21]. The number of the layers also influenced the electrical conductivity; in all the cases, it was evident that the samples with only one layer (0.04 mm to 0.05 mm) displayed the largest value, followed by the second (0.06 mm to 0.08 mm) and third layers (0.08 to 0.11 mm).…”
Section: Electrical Conductivitysupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, the conductivity continued to improve with the increase in the GNP concentration in the paste, which agrees with observations reported in other works [19][20][21]24]. This improvement can be because the incorporation of GNPs has created a path for the electricity flow, and increasing the concentration of the nanoparticles might have resulted in the formation of a better conductive network, which eased the flow of electrons, leading to the linear rise in the electrical conductivity [21]. The number of the layers also influenced the electrical conductivity; in all the cases, it was evident that the samples with only one layer (0.04 mm to 0.05 mm) displayed the largest value, followed by the second (0.06 mm to 0.08 mm) and third layers (0.08 to 0.11 mm).…”
Section: Electrical Conductivitysupporting
confidence: 92%
“…It was observed from Figure 8a,b that the electrical resistivity was reduced, and on the contrary, the electrical conductivity was enhanced, with the addition of GNPs. Additionally, the conductivity continued to improve with the increase in the GNP concentration in the paste, which agrees with observations reported in other works [19][20][21]24]. This improvement can be because the incorporation of GNPs has created a path for the electricity flow, and increasing the concentration of the nanoparticles might have resulted in the formation of a better conductive network, which eased the flow of electrons, leading to the linear rise in the electrical conductivity [21].…”
Section: Electrical Conductivitysupporting
confidence: 90%
See 1 more Smart Citation
“…The higher K/S and lower L* represent the effective reduction of GO that changed the colour of the sample into a darker shade from the lighter shade [15,25]. Furthermore, several authors reported that reduced wool/graphene composites exhibited higher electrical conductivity than silk/graphene, cotton/graphene, and flax/graphene composites, which might be due to the effective chemical bonding among various functional groups of GO and wool [15,48,49]. The electrical conductivity of fabricated WPrGOKF produced in this study was found to be superior to some other reported graphene incorporated fabrics, as shown in Table 2.…”
Section: Electrical Conductivity Of the Knitted Fabricsmentioning
confidence: 99%
“…The use of this product makes it possible to tune both thermal and electrical conductivity of the base material, incorporating graphene nanoplatelets(GNP) as part of the coating or the fibers. Some of the most advanced developments use graphene to manufacture sensors and smart textiles, [21][22][23][24][25][26][27] electromagnetic shielding, [28][29][30] and flexible energy production devices. 31,32 Currently, there are several alternatives to incorporate graphene into textile substrates.…”
Section: Introductionmentioning
confidence: 99%